Measurements of the soft gamma-ray emission from SN2014J with Suzaku - Terada, Yukikatsu; Maeda, K.; Fukazawa, Y.; Bamba, A.; Ueda, Y.; Katsuda, S.; Enoto, T.; Takahashi, T.; Tamagawa, T.; Röpke, Friedrich; Summa, A.; Diehl, R. (The astrophysical journal, 2016)
The hard X-ray detector (HXD) on board Suzaku measured soft γ-rays from the SN Ia SN2014J at 77 ± 2 days after the explosion. Although the confidence level of the signal is about 90% (i.e., 2σ), the 3σ upper limit has been derived at <2.2 × 10−4 ph s−1 cm−2 in the 170-250 keV band as the first independent measurement of soft γ-rays with an instrument other than INTEGRAL. For this analysis, we have examined the reproducibility of the NXB model of HXD/GSO using blank sky data. We find that the residual count rate in the 90-500 keV band is distributed around an average of 0.19% with a standard deviation of 0.42% relative to the NXB rate. The averaged residual signals are consistent with that expected from the cosmic X-ray background. The flux of SN2014J derived from Suzaku measurements taken in one snapshot at t = 77 ± 2 days after the explosion is consistent with the INTEGRAL values averaged over the period between t = 50 and 100 days and also with explosion models of single or double degenerate scenarios. Being sensitive to the total ejecta mass surrounding the radioactive material, the ratio between continuum and line flux in the soft gamma-ray regime might distinguish different progenitor models. The Suzaku data have been examined with this relation at t = 77 ± 2 days, but could not distinguish models between single and double degenerate-progenitors. We disfavor explosion models with larger 56Ni masses than 1 M ⊙, from our 1σ error on the 170-250 keV X-ray flux of (1.2 ± 0.7) × 10−4 ph s−1 cm−2.